Diagnostic potential of blood-based biomarkers in multiple sclerosis - Holm Nielsen, Signe; Karsdal, Morten; Manoel, Bruna; Bay-Jensen, Anne-Christine; Henriksen, Kim (Frontiers in Neurology, 2024)
Multiple sclerosis (MS) is a chronic inflammatory disease affecting the central nervous system (CNS). There is a significant delay in diagnosing MS as the symptoms and tests overlap with other diseases. Blood-based biomarkers, which quantify fragments of proteins involved in MS pathophysiology, have the potential as diagnostic biomarkers. In this study, we evaluated biomarkers by immunoassays, of tissue destruction, reflected by biglycan degraded by matrix metalloproteinases (MMPs) (BGM), cathepsin S-degraded nidogen (NIC), and MMP-degraded secreted protein acidic and rich in cysteine (SPARC-M) in healthy donors and patients diagnosed with MS. The biomarkers were able to separate the two groups with an AUC = 0.710, AUC = 0.765, and AUC = 0.875, respectively. These pathologically released protein fragments could potentially be used as biomarkers in clinical management providing a specific protein fingerprint.